2019
DOI: 10.1002/jcu.22759
|View full text |Cite
|
Sign up to set email alerts
|

Standardization and reproducibility of sonographic stomach position grades in fetuses with congenital diaphragmatic hernia

Abstract: Objectives The purpose of this study was to evaluate the reproducibility of stomach position grading in congenital diaphragmatic hernia (CDH) as proposed by Cordier et al and Basta et al after standardization of the methods at our center. Methods We collected sonographic images from 23 fetuses with left‐sided CDH at our center from 2010 to 2018. Nine operators (one maternal fetal medicine expert and eight sonographers) reviewed the selected images and graded the stomach position according to the methods of Cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 16 publications
3
17
0
Order By: Relevance
“…lowest for "retrocardiac" stomach position (κ = 0.33, 95% CI: 0.18-0.49, p < 0.0001) followed by "mid to posterior" left chest position (κ = 0.52, 95% CI: 0.35-0.69, p < 0.0001) as defined by Basta et al 8 Similarly, fair to moderate inter-operator agreement was also demonstrated for grades 3 (κ = 0.45, 95% CI: 0.27-0.64, p < 0.0001) and 4 (κ = 0.48, 95% CI: 0.30-0.65, p < 0.0001) stomach position, as described by Cordier et al 9 in this series. 13 These findings highlight a potential ambiguity within this stomach classification system and support the need for more precise definitions of these positions for both classifications. 8,9 To help address these ambiguities, we recommend that the AV valves be used as the critical landmark for establishment of stomach position, and that sonographers divide the fetal chest transversely at the AV valves on the four-chamber view of the heart to help classify stomach position.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…lowest for "retrocardiac" stomach position (κ = 0.33, 95% CI: 0.18-0.49, p < 0.0001) followed by "mid to posterior" left chest position (κ = 0.52, 95% CI: 0.35-0.69, p < 0.0001) as defined by Basta et al 8 Similarly, fair to moderate inter-operator agreement was also demonstrated for grades 3 (κ = 0.45, 95% CI: 0.27-0.64, p < 0.0001) and 4 (κ = 0.48, 95% CI: 0.30-0.65, p < 0.0001) stomach position, as described by Cordier et al 9 in this series. 13 These findings highlight a potential ambiguity within this stomach classification system and support the need for more precise definitions of these positions for both classifications. 8,9 To help address these ambiguities, we recommend that the AV valves be used as the critical landmark for establishment of stomach position, and that sonographers divide the fetal chest transversely at the AV valves on the four-chamber view of the heart to help classify stomach position.…”
Section: Discussionmentioning
confidence: 70%
“…The poor interrater agreement between experts for stomach position classification particularly for “mid to posterior” left chest and “retrocardiac” stomach position has also been demonstrated by Ibirogba et al. , 13 in a single center series, which included eight sonographers and an MFM specialist, evaluating stomach position in 23 cases of left CDH. They found that inter‐operator agreement was lowest for “retrocardiac” stomach position ( κ = 0.33, 95% CI: 0.18–0.49, p < 0.0001) followed by “mid to posterior” left chest position ( κ = 0.52, 95% CI: 0.35–0.69, p < 0.0001) as defined by Basta et al 8 .…”
Section: Discussionmentioning
confidence: 81%
“…US1, ultrasound scan ≤24 weeks gestational age (GA); US2, ultrasound scan 24–30 weeks GA; US3 ultrasound scan ≥30 weeks GA. Prenatal liver position “up”: liver intrathoracic. CDH severity: combination of O/E LHR and liver position according to Jani et al 16 …”
Section: Resultsmentioning
confidence: 99%
“…Liver position “up”: liver intrathoracic. CDH severity: combination of O/E LHR and liver position according to Jani et al 16 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation